Tisser dans le désert : interactions et adaptations autour d’un ouvroir missionnaire au Mzab (1892-1950) - Mélina Joyeux (L’Année du Maghreb)
Through a case study centered on the missionary station of Ghardaïa, the largest city of the Mzab region, this paper examines the establishment and the reorganizations of a female Catholic congregation’s mission, the Missionary Sisters of our Lady of Africa – better known as “White Sisters” –, over the course of six decades in close contact with the field. The reception of missionary action among the various components of the local population requires successive adaptations and a long-term investment in the face of scant results. This context led to a chronology that differed from that of other regions of mission such as Kabylia, and to an over-investment in craft activities around the workshop, which served as an opportunity for building interactions over time. Both a technical training center and a craft production facility, it enabled the nuns to work with girls and women, the main targets of their mission. It thus appears as a “world of contact”, in which nuns and Mzab women engage unevenly and with different purposes, redefined throughout the relationship. This missionary action is analyzed through the archives of the White Sisters (diaries and chronicles, annual reports, correspondence, photographs), most of which remain unseen, and those of the Missionaries of Africa or “White Fathers”, the male order to which it is linked. Cross-referenced with archives of the colonial administration and ethnographic literature, these missionary sources enable us to question the way in which the sisters perceived and interpreted these interactions, while at the same time looking for clues to the attitude of the local populations towards the mission.First, the mission is set in its social, political, and religious environment, from the reasons that led the missionary fathers and the colonial authorities to call upon the White Sisters, to the profile of the nuns who settled in a particular colonial society with no specific training. Despite the support of the colonial authorities, their first approach to the local population was marked by misunderstanding and confrontation. Missionary action therefore focused on minorities, quickly nullifying the initial apostolic strategy.At the dawn of the 20th century, the mission was reorganized to place the workshop at the heart of the missionary works. The paper then focuses on the role of weaving in the nuns’ strategy, and how they turned the workshop into a major center for colonial crafts. In doing so, the sisters invested an everyday feminine activity and transformed it in new settings, in line with the development of an imperial economy and colonial policies to promote “indigenous arts”. They appropriated local craft skills and reoriented the production towards the growing tourist market. Focusing first and foremost on the poor, the workshop also had a charitable purpose, with a particular focus on women’s wages. But the article also highlights the ambiguities of such charity faced with constant trade-offs between its different aims and its various audiences.The final section focuses on the limits of these strategies and the pitfalls of missionary action. From the failure to establish a Christian community to the many impasses encountered in reaching Ibadite women or developing school education, the sisters were constantly reinventing their work to perpetuate it. Approaching Mzab society from the margins, they contributed to the disruption and reshaping of relations between the different communities, disrupted by the upset of political, economic, and social balances brought about by colonization. Although they did not achieve the expected results, they gradually acquired a certain familiarity with the Mzab girls and women. These trials and tribulations also reveal forms of resistance to the mission and highlight the Mozabites’ agency in the face of colonial domination.